The impact of exclusive breastfeeding for 6 months and of complementary breastfeeding after 6 months on bone mineral density and bone remodeling - Larissa Brazolotto Ferreira; Keny Gonçalves Tirapeli; Carla Cristiane Silva; José Eduardo Corrente; Tamara Beres Lederer Goldberg (PLoS ONE, 2025)
Objective The aim of this study was to evaluate the evolution of bone mass in exclusive breastfeeding mothers (EBF) for 6 months, and another cohort, who had also exclusively breastfed their children while concomitantly donating breast milk for 6 months (EBF+), with evaluation of their bone mass during the subsequent 6-month period of complementary breastfeeding. Methods A group of exclusive breastfeeding mothers (n = 38) were evaluated at 15 days and six months postpartum, and a second group of EBF-donors (EBF+) (n = 39) were evaluated at six months and one year postpartum. Bone mineral content (BMC) and density (BMD) were evaluated by bone densitometry (DXA) and bone turnover markers were determined: osteocalcin (OC), bone alkaline phosphatase (BAP), and carboxy-terminal telopeptide (S-CTX). Results There was a significant decrease in BMD in the lumbar spine (1.107 ± 0.109 and 1.075 ± 0.112 g/cm2; p < 0.001), total body (1.135 ± 0.086 and 1.119 ± 0.085 g/cm2; p < 0.001), and total proximal femur over the six months of EBF compared to the values obtained from the same EBF group at 15 days postpartum (mean percentage decreases in BMD of −3.4 ± 3.7% (p < 0.001) in lumbar spine, −2.5 ± 3.4% (p < 0.001) in total proximal femur, and −1.7 ± 1.9% (p = 0.001) in total body). For the group of EBF + who practiced complementary breastfeeding after 6 months, densitometric results indicated a tendency to incorporation of bone mass, with a mean percentage increase in BMD of 5.0 ± 3.9% for lumbar spine, and 1.6 ± 3.4% for total proximal femur. Conclusion There was a significant physiological mobilization of bone mineral density in the lumbar spine, total body, and total proximal femur after six months of EBF. In the EBF+ group, even with continued complementary breastfeeding, densitometric results were higher than those observed at 6 months, indicating a continuous increase over time.